Genotypic and Environmental Impacts on Vicine and Convicine Concentrations in Faba Beans - Pankaj Maharjan; Aaron C. Elkins; Jason Brand; Samuel C. Catt; Simone J. Rochfort; Joe F. Panozzo (Agriculture)
High concentrations of vicine and convicine (v-c) in faba beans can trigger favism in susceptible humans, posing a significant barrier to the broader adoption of faba beans as a food source. While plant breeding and various post-harvest processing methods have been adopted to reduce v-c levels, there is limited understanding of how agronomic practices may assist in reducing v-c levels. This study investigated the effect of sowing time (TOS), soil type, and genotype on v-c levels in faba beans. Twelve faba bean genotypes were evaluated across multiple field sites by applying two sowing times and two diverse soil types. The v-c content was quantified using established chromatographic techniques. Genotypes were identified as the most major factor affecting v-c levels, with significant variation observed in mean vicine and convicine contents. Sowing time also had a significant impact (p < 0.01), with lower v-c levels observed in TOS 1 compared to TOS 2. This reduction may be due to a longer plant development period and extended seed desiccation in TOS 1. Soil conditions, likely linked to nutritional factors, significantly influenced vicine concentrations (p < 0.05) but did not influence convicine levels (p > 0.05). These findings highlight the importance of agronomy practices, such as optimal sowing time, soil nutrition, and moisture management, in minimizing v-c levels; the most effective strategy remains the development of low v-c genotypes combined with farming practices that naturally suppress v-c accumulation.